Unification of PBL with RMS: Its influence on critical and creative thinking skills in human respiratory - Karomah, Ana; Ristanto, Rizhal Hendi; Rusdi (Biosfer: Jurnal Pendidikan Biologi, 2025)
Critical and creative thinking skills are two essential aspects in 21st century learning. A simultaneous development of both skills can encourage students to find a correct, varied, and adaptive solution to a problem. This study identifies the influence of the unification of the Problem Based Learning (PBL) with the Reading, Mind mapping, and Sharing (RMS) on students' critical and creative thinking. The PBL and RMS are learning models that have complementary characteristics; therefore, they can be combined in a more effective learning strategy. The research method employs quasi-experimental research with non-equivalent pretest-post-test control groups design.  The research population includes students in Class XI MIPA in 2024/2025 academic year. The sampling uses a simple random sampling technique of 62 students. The research instruments consist of test and non-test instruments comprising 11 and 7 items of essay questions to measure critical thinking skills and creative thinking skills, respectively. The non-test instruments include a Student Worksheet and an observation sheet as secondary data. The pre-requisite test results in normally distributed and homogeneous data. The results of hypothesis test, MANOVA (p<0,05), indicate that the treatment of the unification of PBL with RMS influences student critical and creative thinking skills with a significance value of 0,001 and 0,002, respectively. The implementation of the unification of the PBL with RMS is proven to have a significant influence on student critical and creative thinking skills.